2010
DOI: 10.1111/j.1365-2362.2010.02296.x
|View full text |Cite
|
Sign up to set email alerts
|

Temperature sensitivity of suicidal erythrocyte death

Abstract: Hyperthermia stimulates Ca(2+) entry into erythrocytes leading to cell shrinkage and PS exposure. As PS-exposing erythrocytes are rapidly cleared from circulating blood, the eryptosis during hyperthermia may cause anaemia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
33
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(35 citation statements)
references
References 48 publications
2
33
0
Order By: Relevance
“…However, the finding disagreed with that of Abdelatif et al (2009), who reported higher MCV values in Nubian goats of Sudan during summer than in winter. The decrease in MCV (average size of the erythrocytes) during the HDS may be due to an increase in the number of erythrocyte membrane vesicles formed and shed from the erythrocytes as a result of elevation in body temperature, with a resultant decrease in the size of the parent erythrocytes (Foller et al, 2010;Moore et al, 2013;Habibu et al, 2017). Thus, it is logical to infer that a decrease in MCV may have the potential of being used as an indicator of heat stress in tropical goats naturally exposed to heat stress.…”
Section: Discussionmentioning
confidence: 99%
“…However, the finding disagreed with that of Abdelatif et al (2009), who reported higher MCV values in Nubian goats of Sudan during summer than in winter. The decrease in MCV (average size of the erythrocytes) during the HDS may be due to an increase in the number of erythrocyte membrane vesicles formed and shed from the erythrocytes as a result of elevation in body temperature, with a resultant decrease in the size of the parent erythrocytes (Foller et al, 2010;Moore et al, 2013;Habibu et al, 2017). Thus, it is logical to infer that a decrease in MCV may have the potential of being used as an indicator of heat stress in tropical goats naturally exposed to heat stress.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, exposure to natural heat stress has been reported to cause an increase in MCV of Brazilian Azul goats (Ribeiro et al 2015) and Piemontese cattle (Mazzullo et al 2014). The decrease in MCV during the heat stress of the HDS may be due to an increase in body temperature, which causes an increase in the number of erythrocyte membrane vesicles formed and shed from the erythrocytes with a resultant decrease in the size of the parent erythrocytes (Foller et al 2010;Moore et al 2013). This suggests that decrease in MCV may have the potential of being used as an animal-based indicator of heat stress in tropical goats naturally exposed to heat stress.…”
Section: Haematological Parametersmentioning
confidence: 95%
“…Eryptosis contributes to the pathophysiology of several diseases (29), such as diabetes mellitus, renal insufficiency, iron deficiency, phosphate depletion, hemolytic uremic syndrome, sepsis, sickle cell disease, malaria, Wilson's disease, and presumably metabolic syndrome (7,16,29,32,49,59). Ceramide formation significantly contributes to the stimulation of eryptosis in several of those diseases including hemolytic uremic syndrome, sepsis, fever, and Wilson disease (16,29).…”
mentioning
confidence: 99%
“…Ceramide formation significantly contributes to the stimulation of eryptosis in several of those diseases including hemolytic uremic syndrome, sepsis, fever, and Wilson disease (16,29). Moreover, ceramide-dependent and -independent eryptosis is triggered by a wide variety of small molecules (4 -7, 14, 15, 18, 19, 27, 29, 41, 44, 45, 49).…”
mentioning
confidence: 99%